Enhancing Supply Chain Performance of SMEs in Thailand Using the Integrated Personnel Development Model - Bundit Phrapratanporn; Preecha Wararatchai; Wissawa Aunyawong; Nik Ramli Nik Abdul Rashid (International Journal of Supply Chain Management, 2019)
Personnel development is a salient component of the human resource supply chain of a business organization. This is especially true for small and medium sized enterprises (SMEs) which has limited resources and could potentially affect their supply chain performance. In an era where modern businesses are driven by innovation, a fresh approach to entrepreneur personnel development should be considered crucial and indispensable. Thus, the objective of this study has been to find a comprehensive and multi-dimensional approach in developing outstanding SME entrepreneurs that could bring about enhanced business performance, including in the vital supply chain functions. Through content analysis of relevant literatures in human resources, three pertinent constructs with strong empirical foundations have been identified, namely happy workplace, transformational leadership, learning organization, were selected and later hypothesized to affect organizational commitment and eventually contribute to enhance performance. Questionnaires were used as a quantitative research tool to collect the data from 500 employees in SMEs in the Nakhon Pathom Province, Thailand. Structural Equation Modelling (SEM) was used for analysing the statistics. The results found that the learning organisation is most appropriate, which has direct and indirect effects on supply chain performance. The mediating effect of organisational commitment on the relationship between learning organisation and supply chain performance was also found.Â The results of this study will be beneficial to entrepreneurs, the government, and educational agencies to be used as a guideline to form the policies and conduct further research.